Quality of cheese produced with milk from cows fed forage palm with different forages - Camila Soares (Semina: Ciências Agrárias, 2019)
The objective of this study was to evaluate the effects of forage palm combined with different forages in the diet of F1 Holstein x Zebu cows, on the quality of Minas Frescal cheese. Two simultaneous 4 x 4 Latin squares were used in the experimental design. The treatments consisted of sorghum silage as the sole forage source; replacement of 50% sorghum silage by forage palm; elephant grass as the only forage source; 50% replacement of elephant grass by forage palm. Milk samples from each cow were analyzed for the chemical composition and the milk was pasteurized for cheese production. The gross and adjusted yields, texture, chemical and sensorial characteristics and fatty acid profile were evaluated. The chemical composition of the cheese was not influenced by the diets, as well as the sum of saturated, monounsaturated and polyunsaturated fatty acids. However, a lower stearic acid content was found in cheese from the milk of cows fed grass with forage palm and a lower value of conjugated linoleic acid for the diet with silage alone. In the consumer preference ranking test, the most preferred cheese was that of the sorghum silage diet and the least preferred was that of the sorghum silage/forage palm diet. In the overall impression, higher scores were assigned to cheeses of the treatments with exclusive silage or elephant grass. The replacement of 50% sorghum silage or elephant grass by the forage palm did not change the chemical composition of the Minas Frescal cheese, however, it modified the profile of fatty acids and decreased the acceptance and preference of cheese by the consumers.